PELANGGARAN MAKSIM DALAM FILM 3 SRIKANDI KARYA IMAN BROTOSENO - Virginia Chikita, Lus Antika Vinesia; Patriantoro, Patriantoro; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research examines the violation of maxim in the cooperation principle in film 3 Srikandi by Iman Brotoseno. The purpose of this research is descriptions violation maxim of quantity, violation maxim of quality, violation maxim of relevance, violation maxim of manner, implication, and implementation plan at school. The method used in this research is descriptive method with qualitative research form. Source of data in this research is film 3 srikandi by Iman Brotoseno, and the data in the form of speeches containing violations of maxim in the cooperation principle. Based on data analysis result found violation maxim of quantity there are 48 data, violation maxim of quality there are 9 data, violation maxim of relevance there are 36 data, and violation maxim of manner there are 9 data. The violations of maxim committed by the characters in the film 3 Srikandi have a certain intention behind the speech that caused the implicatur. The results of this research can be applied in schools in Indonesian language and literature learning at the level of SMA/MA/SMK class XI even semester. Keywords: violation of maxim, cooperation principle, film 3 Srikandi, Iman Brotoseno.